2007
DOI: 10.1063/1.2434155
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between sterically stabilized nanoparticles in supercritical fluids: A simulation study

Abstract: The authors report a simulation study of the interaction between gold nanoparticles stabilized with both linear and branched alkane chains in supercritical ethane. In agreement with experimental and previous theoretical work, the authors find that increasing solvent density and making ligands more branched make the nanoparticle interaction more repulsive. These findings are analyzed in terms of the extent of the chain interdigitation and chain-solvent interaction energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 26 publications
6
62
2
Order By: Relevance
“…[18][19][20][21] It is important to note that the effective NC-NC interactions in a solvent are very different from the ones in vacuum due to solvent-capping layer interactions. The work of Patel and Egorov 22 focused on the PMF for very small capped NC cores ͑Au 38 ͒ for varying solvent quality, and it was found that the PMF can be tuned from strongly attractive to fully repulsive. In our previous work, we have shown for one system that the interaction between alkylthiol capped NCs becomes purely repulsive in a good solvent ͑n-hexane͒; 23 we are currently investigating in detail the NC-NC interactions in different solvents at different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] It is important to note that the effective NC-NC interactions in a solvent are very different from the ones in vacuum due to solvent-capping layer interactions. The work of Patel and Egorov 22 focused on the PMF for very small capped NC cores ͑Au 38 ͒ for varying solvent quality, and it was found that the PMF can be tuned from strongly attractive to fully repulsive. In our previous work, we have shown for one system that the interaction between alkylthiol capped NCs becomes purely repulsive in a good solvent ͑n-hexane͒; 23 we are currently investigating in detail the NC-NC interactions in different solvents at different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As the nanoparticles approach closer, chains enter the region between particles and align into blocks on each nanoparticle and then lie parallel to those on opposite nanoparticles, making an extended ordered block. There appears to be little apparent interdigitation of individual chains from opposite nanoclusters as was reported by Patel & Egorov (2007). At the short end of this range (approx.…”
Section: (A) Qualitative Descriptionmentioning
confidence: 54%
“…As the nanoparticles approach more closely, chains from opposite particles move into the inter-particle region. Patel & Egorov (2007) describe the interaction between opposing chains as interdigitation. However, the behaviour we observe is not well described by this term; we observe a lateral co-alignment of the aligned blocks on opposing nanoparticles (figure 1d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] Due to high computational cost, only few studies investigated properties of systems with several NCs. 16,20,21 The NCs in those studies were relatively small (up to 140 atoms) compared to the ones typically used in assembly experiments. 12 Recent simulation studies 19,21 show, in addition, that the presence of solvent strongly influences the structure of capping layers.…”
Section: 13mentioning
confidence: 99%